Exploring Lower Secondary Students’ Mathematical Literacy in Number Content Through the Lens of Logical Mathematical Intelligence - Aisiya, Dina Nur; Suryanti, Sri (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2026)
Although research on mathematical literacy and multiple intelligences has advanced significantly, studies that specifically examine the characteristics of junior high school students’ mathematical literacy in PISA number content through logical mathematical intelligence remain very limited. This study aims to describe the characteristics of junior high school students’ mathematical literacy with different levels of logical mathematical intelligence in solving PISA equivalent problems, as well as to analyze the relationship between the level of logical mathematical intelligence and the problem solving strategies demonstrated by students. This study was designed using a descriptive qualitative approach and involved thirty four junior high school students selected through purposive sampling based on high, medium, and low levels of logical mathematical intelligence;research instruments included a multiple intelligence test, number content questions adapted from PISA, and a semi-structured interview guide;data analysis was conducted through the stages of data reduction, data presentation, and drawing conclusions using the triangulation method. The results of the study indicate that logical mathematical intelligence is related to mathematical literacy:students with high intelligence demonstrated comprehensive problem formulation accompanied by multivariable evaluation strategies;students with medium intelligence were able to identify relevant information but were limited to a single variable without thorough verification; and students with low intelligence still relied on procedural intuition accompanied by fundamental misunderstandings. These findings support the premise that logical mathematical intelligence not only determines the accuracy of the final answer but also shapes the depth of students’ overall mathematical cognitive processes. Further research is recommended to expand the content beyond numbers.